PENGATURAN KEBIJAKAN PEMERINTAH INDONESIA MENGENAI TATA NIAGA IMPOR PANGAN - Sihabudin Sihabudin (Arena Hukum, 2015)
AbstractPolicy is a government decision that is general and preveils to all people. The legal consequences of being a member of the world trade organization is that the Indonesian government must take submissive and obedient to the rules agreed in international trade agreements related to exports and imports, including making changes to the legal instruments and policy development in the trade sector. The marketing of rice and several other food commodities involving import has dimensions that are not simple problems, even multi-dimensional, ranging from economic, political, as well as socio-cultural.Indonesian government's policies regarding the regulation of food import regulation is an effort to protect domestic manufacturers from dumping activities or due to increased imports, Indonesia is also to protect consumers from imported products that do not meet the quality standards of security and health of consumers.This paper is about to do a reformulation of the government's policy regarding the adjustment of the trade system for food imports, in order to find effective policy formulation and efficient in solving the problems that arise regarding the marketing of food imports that has been happening. By using descriptive normative legal analysis, the study found that the common thread of chaos cross trade system for food import regulations which are due to unfitted between national regulations and regional regulations (AFTA, CAFTA, APEC) as well as global regulations (GATT-WTO). Thus, administrative reform of domestic and foreign trade are necessary, particularly regarding to the procedure of rice imports. All forms of deviations in import licensing process, document manipulation, and the pattern of non-governmental practices must obtain decisive action, both administratively and legally, as a valuable shock-therapy.Â AbstrakKebijakan adalah keputusan pemerintah yang bersifat umum dan berlaku untuk seluruh anggota masyarakat. Konsekuensi hukum dari menjadi anggota organisasi perdagangan dunia adalah bahwasanya pemerintah Indonesia harus ikut tunduk dan patuh pada kaidah-kaidah yang disepakati dalam persetujuan perdagangan internasional terkait ekspor-impor, termasuk melakukan perubahan terhadap instrumen hukum dan kebijaksanaan pembangunan di sektor perdagangan. Tata niaga beras dan beberapa komoditas pangan lain yang melibatkan impor memiliki dimensi permasalahan yang tidak sederhana, bahkan multi-dimensi, mulai dari ekonomi, politik, bahkan sosio kultural. Kebijakan pemerintah Indonesia mengenai pengaturan tata niaga impor pangan merupakan upaya melindungi produsen dalam negeri dari kegiatan dumping atau karena meningkatnya produk impor, juga untuk melindungi konsumen Indonesia dari produk impor yang tidak memenuhi standar kualitas keamanan dan kesehatan konsumen. Tulisan ini hendak melakukan reformulasi kebijakan pemerintah mengenai pengatuan tata niaga impor pangan, agar ditemukan rumusan kebijakan yang efektif dan efisien dalam menyelesaikan problematika yang muncul seputar tata niaga impor pangan yang selama ini terjadi. Dengan menggunakan analisis hukum normatif deskriptif, penelitian ini menemukan bahwa benang merah dari silang sengkarut regulasi tata niaga impor pangan diantaranya adalah karena tidak sinkronnya antara regulasi nasional dengan regulasi regional (AFTA, CAFTA, APEC) maupun regulasi global (GATT-WTO). Sehingga, diperlukan pembenahan administrasi perdagangan dalam negeri dan perdagangan luar negeri, khususnya yang berhubungan dengan prosedur impor beras. Segala bentuk penyimpangan dalam proses perizinan impor, manipulasi dokumen, dan pola praktik non-pemerintah perlu memperoleh tindakan tegas, baik secara administratif, maupun secara legal, sebagai shock-therapy yang berharga.Â